HYDROLYSIS OF PROTEINS AND NUCLEIC ACIDS BY LANCEFIELD GROUP A AND OTHER STREPTOCOCCI - Deibel, R. H. (1963)
Deibel, R. H. (American Meat Institute Foundation, Chicago, Ill.). Hydrolysis of proteins and nucleic acids by Lancefield group A and other streptococci. J. Bacteriol. 86:1270–1274. 1963.—Classically, group A streptococci have been considered to be nonproteolytic in spite of the observation that a proteinase is produced in broth cultures. When tested by the plate method, it was observed that 78% of 47 strains were proteolytic when the cultures were incubated anaerobically. Some strains hydrolyzed gelatin aerobically; however, the hydrolysis of casein and pepsin required anaerobic conditions of growth. Other proteins hydrolyzed included wheat gluten and a beef-muscle preparation. The hydrolysis of bovine serum albumin, lactalbumin, sheep plasma, and lysozyme was not detected in plate cultures. The hydrolysis of deoxyribonucleic acid and ribonucleic acid was characteristic of the majority of the strains. Unlike the proteolytic activity, the nucleolytic activity was independent of oxygen tension. Other streptococci were screened for hydrolytic activity; among these strains, only the single strain of Streptococcus sanguis tested possessed proteolytic activity. Deoxyribonuclease activity was observed in “animal” but not “human” group C strains, and in some strains of groups G and L.